![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{2}.2^n+4.2^n=9.2^5\Rightarrow2^n\left(\frac{1}{2}+4\right)=288\Rightarrow2^n.\frac{9}{2}=288\Rightarrow2^{n-2}.9=288\Rightarrow2^{n-2}=32\)(dấu "=>" số 3 bn sửa thành 2n-1.9=288=>2n-1=32 nha)
=>2n-1=25=>n-1=5=>n=5+1=6
vậy......
~~~~~~~~~~~~~~~
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 9.27n = 35
=> 32.33n = 35
=> 32 + 3n = 35
=> 2 + 3n = 5
=> 3n = 5 - 2
=> 3n = 3
=> n = 1
b) (23 : 4).2n = 4
=> 2.2n = 4
=> 2n = 4 : 2
=> 2n = 2
=> n = 1
c) 3-2.34 . 3n = 37
=> 3-2 + 4 + n = 37
=> 32 + n = 37
=> 2 + n = 7
=> n = 7 - 2 = 5
d) 2-1.2n + 4.2n = 9.25
=> (1/2 + 4).2n = 9.25
=> 9/2.2n = 9.25
=> 2n = 9.25 : 9/2
=> 2n = 26
=> n = 6
\(a,9\cdot27^n=3^5\)
\(\Rightarrow9\cdot27^n=243\)
\(\Rightarrow27^n=243:9=27\)
\(\Rightarrow27^n=27^1\)
\(\Rightarrow x=1\)
\(b,\left(2^3:4\right)\cdot2^n=4\)
\(\Rightarrow\left(8:4\right)\cdot2^n=4\)
\(\Rightarrow2\cdot2^n=4\)
\(\Rightarrow2^n=4:2=2\)
\(\Rightarrow n=1\)
\(c,3^{-2}\cdot3^4\cdot3^n=3^7\)
\(\Rightarrow3^2\cdot3^n=3^7\)
\(\Rightarrow3^n=3^7:3^2=3^5\)
\(\Rightarrow n=5\)
\(d,2^{-1}\cdot2^n+4\cdot2^n=9\cdot2^5\)
\(\Rightarrow2^n\cdot\left(2^{-1}+4\right)=9\cdot32\)
\(\Rightarrow2^n\cdot\frac{9}{2}=288\)
\(\Rightarrow2^n=288:\frac{9}{2}=64\)
\(\Rightarrow2^n=2^6\)
\(\Rightarrow n=6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(10^{n+1}-6.10^n\)
\(=10^n.10-6.19^n\)
\(=10^n.\left(10-6\right)\)
\(=10^n.4\)
b) \(2^{n+3}+2^{n+2}-2^{n+1}+2^n\)
\(=2^n.2^3+2^n.2^2-2^n.2+2^n.1\)
\(=2^n.\left(2^3+2^2-2+1\right)\)
\(=2^n.11\)
c) \(90.10^k-10^{k+2}+10^{k+1}\)
\(=90.10^k-10^k.10^2+10^k.10\)
\(=10^k.\left(90-10^2+10\right)\)
\(=0\)
d) \(2,5.5^{n-3}.10+5^n-6.5^{n-1}\)
\(=\dfrac{2,5.5^n.10}{5^3}+5^n-\dfrac{6.5^n}{5}\)
\(=\dfrac{5^n}{5}+5^n-\dfrac{6.5^n}{5}\)
\(=\dfrac{5^n+5^{n+1}-6.5^n}{5}=\dfrac{5^n+5^n.5-6.5^n}{5}=\dfrac{5^n\left(1+5-6\right)}{5}=\dfrac{0}{5}=0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
B = \(\left(2^4\right)^n+4=16^n+4=...6+4=...10\text{ }⋮\text{ }10\)
C = \(\left(9^2\right)^n+3=81^n+3=...1+3=...4\text{ }⋮\text{ }2\)